Bacterial Quality and Molecular Detection of Food Poisoning Virulence Genes Isolated from Nasser Lake Fish, Aswan, Egypt - Nady Khairy Elbarbary; Mohamed K. Dandrawy; Ghada Hadad; Maha Abdelhaseib; Amna A. A. Osman; Rawaf Alenazy; Ibrahim Elbagory; Neveen M. Abdelmotilib; Fagelnour Elnoamany; Ghada A. Ibrahim; Reda A. Gomaa (International Journal of Food Science)
The microbial analysis of fish is critical for ensuring overall health. Uncooked fish can serve as a conduit for transmitting several types of microbes; the current investigation sought to assess the bacterial levels in various kinds of fish from Nasser Lake, Aswan, Egypt, considered the chief source of potable water in Egypt. Two hundred and fifty fish samples, including 50 of each Oreochromis niloticus, Sander lucioperca, Lates niloticus, Clarias gariepinus, and Mormyrus kannume, from Nasser Lake, Aswan, Egypt, were collected to detect the bacterial load, isolation, and identification of Aeromonas hydrophila, Pseudomonas aeruginosa, and Vibrio parahaemolyticus and their virulence genes. The findings revealed that Oreochromis niloticus and Clarias gariepinus exhibited higher bacterial loads than other fish species. Incidences of bacterial contamination among examined fishes were 28.8%, 20.4%, and 16% for Aeromonas hydrophila, Pseudomonas aeruginosa, and Vibrio parahaemolyticus, respectively. Additionally, PCR analysis detected the presence of aerA (60%) and Act (40%) genes in A. hydrophila, rpoB (70%) and LasB (30%) genes in P. aeruginosa, and ToxR (70%) and tdh (50%) genes in V. parahaemolyticus. The study suggested that the bacterial contamination levels in Oreochromis niloticus and Clarias gariepinus could be notably more significant than in other species that could potentially be harmful to the consumers, especially considering the identification of particular bacteria known to cause foodborne illnesses. Further recommendations emphasized that regular monitoring and assessments are required to preserve their quality.